PENGENDALIAN QUADCOPTER MENGGUNAKAN CC3D FLIGHT CONTROLLER - Zoel Fachri; Muhammad Ichsan (J-Innovation, 2022)
Quadcopter technology is currently growing rapidly and is widely used in various needs, both in the fields of education, military, multimedia, health and others. In the quadcopter flight phase at a certain altitude critical phases often occur such as shocks and instability due to external influences such as wind. These problems make research to control the quadcopter in maintaining a stable altitude and movement with roll, pitch and yaw positions. Quadcopter control to produce stability is set using a PID control system with these parameter values processed into the CC3D Flight Controller as well as error feedback from the gyroscope and accelerometer sensors. The results of the study show that a quadcopter using the CC3D flight controller can maintain a flight altitude of 15 meters with a value of KP = 0.0030, Ki = 0.000050 and Kd = 0.0030.